Evaluation of strength between high level male and female athletes - Giannoulaki, C.; Koutidis, A.; Gannoylaki, A.; Goulas, P.; Komsis, S.; Bekris, E.; Gioldasis, A. (Global journal for research analysis, 2017)
The evaluation of strength is very important for elite athletes. The strength is directly related to athletics as well as is essential for achieving high-performance in sports. The purpose of this study was to evaluate the strength in elite athletes in relationship to their gender. In this research participated 12 athletes especially runners and jumpers (6 men and 6 women) with distinctions in sport. The maximum Isometric, Eccentric and Concentric force of the lower limbs was measured. The instruments used were one multyjoint isokinetic machine type (hydromechanics SA), located in the Sports Biomechanics Laboratory (DAC) of the Physical Education. Serres, for the measurement of isometric, the eccentric and concentric force. The study was conducted in the laboratory biokinetics (ODA) of Physical Education Serres. The results showed that there were statistically significant differences between men and women in body weight in body height, the maximum isometric strength, the maximum concentric force, the maximum eccentric force,